2016
DOI: 10.1038/srep27769
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity Promotes Diabetic Nephropathy in Rodent Offspring

Abstract: Maternal obesity is known to increase the risk of obesity and diabetes in offspring. Though diabetes is a key risk factor for the development of chronic kidney disease (CKD), the relationship between maternal obesity and CKD has not been clearly defined. In this study, a mouse model of maternal obesity was employed to determine the impact of maternal obesity on development of diabetic nephropathy in offspring. Female C57BL/6 mice were fed high-fat diet (HFD) for six weeks prior to mating, during gestation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 52 publications
4
39
0
Order By: Relevance
“…Several factors have been shown to contribute to the progression of diabetic nephropathy; hyperglycemia, hypertension, obesity and advancing age have been extensively characterized (2,3). However, the precise mechanism for this condition remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been shown to contribute to the progression of diabetic nephropathy; hyperglycemia, hypertension, obesity and advancing age have been extensively characterized (2,3). However, the precise mechanism for this condition remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, maternal obesity increases the offspring's risk of dysglycemia, diabetes, and hypertension, which may propagate renal dysfunction in later life (4). We demonstrated that the offspring of obese dams have increased renal damage, including renal fibrosis, inflammation, and oxidative stress changes (29). Compared to the offspring of lean mice, we observed significantly worse renal function and albuminuria in the offspring of obese dams.…”
Section: Fetal Programming Maternal Transmission Of Disease and Epimentioning
confidence: 67%
“…Compared to the offspring of lean mice, we observed significantly worse renal function and albuminuria in the offspring of obese dams. While this effect occurred independently of the development of diabetes, renal function and urinary albumin excretion were significantly exacerbated when the offspring also developed diabetes (29). Epidemiologic data in humans support the association of maternal obesity with the development of CKD in the offspring, although data are limited.…”
Section: Fetal Programming Maternal Transmission Of Disease and Epimentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing the same rodent model of maternal obesity, we then showed similar metabolic changes and kidney histological features in male offspring from obese mother at postnatal week 32, especially in the offspring exposed to diet‐induced obesity (HFD‐feeding throughout adulthood) and streptozotocin‐induced diabetes . We found offspring from obese mother had impaired glucose tolerance, higher retroperitoneal and epididymal fat depositions ( P < 0.01 vs control) despite similar body weight, alongside higher serum creatinine levels, 24 h urinary albumin creatinine ratio, worse renal tubular injury and glomerulosclerosis scores when compared to offspring from lean mothers . These findings suggest maternal obesity has significant adverse effects on the offspring’s kidneys across the lifespan, from early in postnatal life (days 1 and 20), persistent to middle adulthood (week 32).…”
Section: Evidence Of Maternal Obesity‐induced Kidney Damage In Offspringmentioning
confidence: 70%